LARGE SOLITARY ENCAPSULATED NEUROFIBROMA OF UPPER ARM – A CASE REPORT - Terzic, Zoran; Radonjic, Dubravka; Paunovic, Marinko; Ljaljevic, Agima; Bojic, Miloš (Sanamed, 2022)
Introduction: Neurofibromas are benign tumors of neuronal origin, occurring most commonly in young adults, with no gender predilection. The connection of neurofibroma with disorders on a general level as von Recklinghausen’s disease makes its diagnosis critical. Case report: A 32-old female patient was administered to the Clinic of Plastic surgery, Clinical Center of Montenegro in Podgorica, with a 10-year history of painless, subcutaneous tumor of the right upper arm that grew in size over the last ten years. The patient reported progressive pain and tingling in her right forearm and right hand for the last 12 months. An MRI showed a non-homogenous tumor of the middle third portion of the triceps muscle, in close contact with the humerus but without infiltrating it. The tumor was removed, with a definitive histopathological result of a solitary benign neurofibroma. Conclusions: This example of successful treatment of solitary neurofibroma may serve to increase the awareness of surgeons and radiologists in small countries regarding benign peripheral nerve sheath tumors. The patient is under observation for two years with no signs of relapse and no other features indicative of neurofibromatosis type 1.